Arrangement of the Clostridium baratii F7 toxin gene cluster with identification of a σ factor that recognizes the botulinum toxin gene cluster promoters. - Nir Dover; Jason R Barash; Julianne N Burke; Karen K Hill; John C Detter; Stephen S Arnon (PLoS ONE, 2014)
Botulinum neurotoxin (BoNT) is the most poisonous substances known and its eight toxin types (A to H) are distinguished by the inability of polyclonal antibodies that neutralize one toxin type to neutralize any of the other seven toxin types. Infant botulism, an intestinal toxemia orphan disease, is the most common form of human botulism in the United States. It results from swallowed spores of Clostridium botulinum (or rarely, neurotoxigenic Clostridium butyricum or Clostridium baratii) that germinate and temporarily colonize the lumen of the large intestine, where, as vegetative cells, they produce botulinum toxin. Botulinum neurotoxin is encoded by the bont gene that is part of a toxin gene cluster that includes several accessory genes. We sequenced for the first time the complete botulinum neurotoxin gene cluster of nonproteolytic C. baratii type F7. Like the type E and the nonproteolytic type F6 botulinum toxin gene clusters, the C. baratii type F7 had an orfX toxin gene cluster that lacked the regulatory botR gene which is found in proteolytic C. botulinum strains and codes for an alternative σ factor. In the absence of botR, we identified a putative alternative regulatory gene located upstream of the C. baratii type F7 toxin gene cluster. This putative regulatory gene codes for a predicted σ factor that contains DNA-binding-domain homologues to the DNA-binding domains both of BotR and of other members of the TcdR-related group 5 of the σ70 family that are involved in the regulation of toxin gene expression in clostridia. We showed that this TcdR-related protein in association with RNA polymerase core enzyme specifically binds to the C. baratii type F7 botulinum toxin gene cluster promoters. This TcdR-related protein may therefore be involved in regulating the expression of the genes of the botulinum toxin gene cluster in neurotoxigenic C. baratii.